Analysis of Traffic Accidents Before and During Covid 19 Pandemic and Alternative Countermeasures on Daan Mogot Road - Budiman, Arief; Intari, Dwi Esti; Sukmana, Raihan Afif (Jurnal Fondasi, 2023)
Daan Mogot Road is a national road that connects West Jakarta and Tangerang City which is always passed by many road users every day like motorcycles, cars, and trucks as well as public transportation such as city transport and bus. According to the data from the Traffic Unit of Tangerang City Police Station in the year 2018, there are 45 cases of traffic accidents, in the year of 2019 there are 29 cases of traffic accidents, in the year of 2020 there are 37 cases of traffic accidents and in the year of 2021 there are 34 cases of traffic accidents on Daan Mogot Road. Within 3 years there were 145 cases of accidents occurred on the Daan Mogot Road. Therefore, Daan Mogot Road was chosen as the area to be evaluated for road safety to know the cause of accidents and accident rate seen from various aspects so that alternative countermeasures can be provided. There are three methods used in this study, Accident Equivalent Rate and Upper Control Limit to analyze accident-prone areas and The Gross Output (Human Capital) method to count accident victim costs. According to the inspection of accident data, segments 3 and 4, or Kel. Tanah Tinggi and Kel. Batuceper in Tangerang City has the highest accident rate of the five Daan Mogot sections. The human factor is the main factor of accidents in every segment. Front-rear collisions are the most common type of accident, followed by side-to-side collisions and pedestrian collisions.